PEMAHAMAN GENERASI MUDA ATAS LEKSIKON TUMBUHAN PAKAN TERNAK DI DUSUN BANGELAN, KECAMATAN WONOSARI, KABUPATEN MALANG - Mahmudah, Hidayatul (University of Brawijaya, 2022)
This study aims to reveal the understanding of the younger generation of the animal feed plant lexicon in the Bangelan Hamlet, Bangelan Village, Wonosari District, Malang Regency. The instrument that was made for this study consisted of 2 questionnaires, namely displaying a lexicon of fodder plants with pictures and without images. This research uses quantitative descriptive methods. Research respondents were 20 respondents, who were taken from the younger generation of 12-22 years in Bangelan Hamlet, Bangelan Village, Wonosari District, Malang Regency. The results of this study indicate that the young generation's understanding of the animal feed plant lexicon based on questionnaire 1 (without pictures) results obtained good categories of 5%, 30% enough, less 35%, and very less categories of 30%. Meanwhile, the overall recapitulation of the understanding of the younger generation of Bangelan Hamlet over TPT with questionnaire 2 (with pictures) is as follows: good category 30%, enough category 40%, 0% less category, and very less 0% category. The results of the calculation of the two questionnaires showed that respondents' knowledge of lexically animal feed plants was still relatively low. The findings in this study are found in the